Microbial and physicochemical water quality changes within distribution and premise plumbing systems during a chlorine conversion. - Helen Y Buse; Jatin H Mistry (PLOS Water)
A strategy for nitrification control within chloraminated drinking water systems (CDWSs) is to temporarily switch from chloramine secondary disinfection to free chlorine, also known as a free chlorine conversion (FCC). However, the long-term and beneficial effects of FCCs are unclear, especially regarding opportunistic pathogen occurrence. In this study, the impacts to microbial and physicochemical parameters were monitored throughout a CDWS implementing a FCC. Water samples were collected weekly for 4-6 weeks before, during, and after a FCC at eight locations: four distribution system and four residential sites. Monochloramine residual (mean±standard deviation) before and after the FCC averaged 1.8±0.9 and 1.6±1.0 parts per million (ppm) for all sites, respectively. Free chlorine levels averaged 2.3±0.9 ppm. There were no significant differences in turbidity and hardness at each location during the three time periods, but some were noted for pH, temperature, and orthophosphate levels across various sites and sampling periods. For all locations, heterotrophic plate count levels were lower during the FCC compared to the periods before and after. All samples from one residence were culture positive for P. aeruginosa which exhibited high levels before the FCC, decreasing levels during, and steadily increasing levels after. Additionally, one week prior to the FCC, sediment samples from two elevated storage tanks, ET-1 and ET-2, were analyzed with ET-1 displaying higher levels of culturable heterotrophic bacteria and molecularly detected total bacteria, Legionella spp., and nontuberculous mycobacteria (NTM), as well as presence of culturable P. aeruginosa and total coliforms compared to ET-2. Fourteen P. aeruginosa and total coliform isolates were whole genome sequenced with genetic differences observed depending on the sampling location and timepoint. Collectively, the observed differences in chemical and microbial parameters advocates for a better understanding of the effects associated with implementing FCCs to determine both their effectiveness and potential risks/rewards to water quality.